Political Marketing Management of Parliament Under the Presidential Government System: A Lesson Learned from the Indonesia House of Representative Post–New Order Soeharto. Issue 2 (3rd April 2017) - Ahmad, Nyarwi
Abstract : Modern political marketing management of parties, government, and parliament have gradually taken place within and across democratic countries ruled under either the parliamentary government or presidential government systems. Little attention, however, has been directed to the extent to which modern political marketing management of parliament has taken place within countries run under the presidential system of government, especially Indonesia. As led by hypothetical-inductive approach, this work has been specifically directed to explore (1) the dynamic exchanges and interactions; (2) the nature and structure of political market arenas; (3) types of political products; and (4) models of political marketing management of the Indonesian parliament/the Indonesian House of Representatives. This work explores the extent to which institutional marketing management strategies have been advanced by the Indonesian Parliament/the Indonesian House of Representatives since Post–New Order Soeharto up to the Susilo Bambang Yudhoyono (SBY) government era (2004 to 2014).